The accute effects of resistance exercise on intraocular pressure - Vieira,Geraldo Magela (2003)
PURPOSE: To study intraocular pressure (IOP) variations in healthy volunteers after weight lifting, in the supine position. METHODS: A descriptive study was designed. Thirty-four individuals were preselected for this study, and a group of 25 volunteers fulfilled the inclusion criteria for joining the initial phase of this research. All of them were healthy without glaucoma. They were asked to lift an 85% top load in the supine position for 8 times. IOP was measured before and after the exercise. Student's t test was used to analyze the IOP variations. RESULTS: A small, but significant IOP decrease (1.61 mmHg) was obtained after exposing 25 individuals (49 eyes) to a specific physical effort. CONCLUSIONS: After a session of weight lifting in the supine position with 85% top load for 8 repetitions, there is a small, but significant IOP decrease.